The Effect of the Use of Quick Response Indonesia Standard (QRIS) on the Development of Micro, Small and Medium Enterprises (MSMEs) in Langsa City - Kautsar, Muhammad Haris; Nurjanah, Nurjanah; Yahya, M; Muhammad, Alfian (Journal of Islamic Financial Technology, 2024)
In the digital era, Micro, Small and Medium Enterprises (MSMEs) in Langsa City face challenges to adapt to the growing non-cash payment technology. This study aims to analyze the effect of ease of use, understanding of benefits, and income expectations on MSME development through the implementation of the Quick Response Code Indonesian Standard (QRIS). The research method used is quantitative with regression analysis techniques to test the partial and simultaneous effects of the independent variable on the dependent variable. The results showed that ease of use (tcount = 4.351), usefulness (tcount = 3.772), and income expectations (tcount = 3.887) had a positive and significant effect partially on the development of MSMEs. Simultaneously, the three variables also showed a significant effect with an Fcount value of 16.204 which exceeded the Ftable of 2.47, with a significance level of 0.000 0.05. This finding confirms the importance of improving QRIS literacy and adoption to support MSME growth. The implication is that strategic policies such as training, socializing the benefits of QRIS, and providing supporting facilities need to be designed to create an ecosystem conducive to the development of MSMEs in Langsa City.